Dissociation and ionization of an HD+ beam induced by intense 395-nm ultrashort laser pulses - McKenna, J.; Sayler, A. M.; Gaire, B.; Johnson, Nora G.; Parke, E.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, I. (My University, 2009)
The majority of research on intense (∼1014 W/cm2) ultrashort (<100 fs) laser-molecule interactions has been focused on studies of H+2 fragmentation, mainly due to its elemental structure. So far the bulk of this work has been conducted using near infrared light while studies at shorter wavelengths are comparatively scarce. We report a detailed investigation of the interaction of 395 nm, 40 fs pulses with an HD+ molecular-ion beam, measured using a coincidence three-dimensional momentum imaging technique. This allows us to clearly discriminate dissociation and ionization channels. From the kinetic energy and angular distributions, insight is gained into the intensity dependence of the main breakup processes. We observe the onset of above-threshold dissociation above 1014 W/cm2, a higher intensity than required for 790 nm due to a smaller transition dipole moment for the low vibrational states probed at 395 nm. Ionization spectra display structure consistent with the above-threshold Coulomb explosion mechanism that we have proposed [B. D. Esry et al., Phys. Rev. Lett. 97, 013003 (2006)].